KAJIAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR DI SMK - Reza Kusuma; setuju (Universitas Sarjanawiyata Tamansiswa Yogyakarta, 2025)
is a study that uses the method of literature study or literature review. The subject of study is effectiveness, learning outcomes, and STAD type cooperative learning methods. The data collection method is the documentation method. Data analysis in this study is bibliographic annotation analysis. The review procedures used in this research are: (1) Organize; (2) Synthesize; (3) Identify; and (4) Formulates. Obtained studies prove that (1) the use of the STAD type cooperative learning model can increase student motivation. The application of the STAD type cooperative learning model emphasizes interaction between students to motivate and help each other to be able to master the material and achieve maximum efficiency, and is also a simple and good cooperative learning method or approach for teachers who are just starting to work together in class, STAD also an effective cooperative learning method. (2) The STAD type cooperative learning model is the best model for achieving learning objectives and activating students through a combination of lecture, question and answer and discussion methods. Then the results of studies carried out by more than one researcher also show that learning with a collaborative system or STAD is said to be able to make improvements in student learning outcomes..Keywords: :